Nowhere boy [videorecording (DVD)] - Taylor-Johnson, Sam, 1967-; Taylor-Johnson, Aaron, 1990-; Duff, Anne-Marie; Threlfall, David; Scott-Thomas, Kristin, 1960- (Sony Pictures Home Entertainment, 2011)
Set in Liverpool in 1955, the adolescent years of John Lennon are chronicled. Raised by his Aunt Mimi, his world is turned inside-out when his free spirited mother re-enters his life, opening up old wounds that release pain, anger, frustration, and his artistry.